2021
DOI: 10.5624/isd.20200313
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cone-beam computed tomographic sialography in the diagnosis and management of primary Sjögren syndrome: Report of 3 cases

Abstract: Sjögren syndrome is a chronic autoimmune inflammatory disease characterized by lymphocytic infiltration of exocrine glands, predominantly the parotid and lacrimal glands, thereby resulting in oral and ocular dryness. It has been reported to occur most frequently in women between 40 and 50 years of age. Sjögren syndrome has an insidious onset, is slowly progressive, and presents a wide range of clinical manifestations, leading to delays or challenges in the diagnosis. Early diagnosis of this condition is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This facilitates the identification of specific anatomical changes, and it is more cost-effective and convenient for patients. [44][45][46] However, the ability to detect early or small lesions might be overlooked. 47 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This facilitates the identification of specific anatomical changes, and it is more cost-effective and convenient for patients. [44][45][46] However, the ability to detect early or small lesions might be overlooked. 47 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This was because conventional parotid imaging has better resolution and generates clearer images of the parotid structures. This facilitates the identification of specific anatomical changes, and it is more cost‐effective and convenient for patients 44–46 . However, the ability to detect early or small lesions might be overlooked 47 …”
Section: Discussionmentioning
confidence: 99%
“…By allowing detailed exploration of the ductal tree and late evacuation imaging, it provides assessment of salivary gland function and obstructive conditions [ 11 , 12 ]. Three-dimensional (3D)-cone-beam computed tomography (CBCT) sialography is becoming increasingly common as it provides fast high spatial resolution 3D images of the ductal system [ 13 , 14 ]. Several studies have shown the superiority of 3D-CBCT sialography compared to conventional sialography for visualization of ducts up to the 6th branch of division and for detection of stenosis and sialolithiasis [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sialography was initially described in 1902 by Carpy and remains the most accurate method for imaging the salivary ductal system. It provides a cost effective and safe diagnostic solution that can be routinely employed as a screening procedure for salivary gland pathologies, namely aberrations in the ductal system, sialoliths and Sjögren’s syndrome [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%